Reinforcing Legal Enforcement Mechanisms in Environmental Pollution Control: An Analysis of Regulatory Effectiveness in River Basin Areas - Bimadiguna Kharisma Adyasta, Muhammad (LPPM Universitas Harapan Bangsa, 2025)
Environmental pollution in river basin areas is a systemic ecological problem caused by industrial, domestic, and agricultural waste that contaminates water bodies and disrupts ecosystem functions. This study aims to analyze the effectiveness of legal enforcement in addressing environmental pollution in river basins and to formulate strategies for strengthening legal mechanisms. The research employs a normative juridical method with statutory and conceptual approaches, utilizing primary, secondary, and tertiary legal materials analyzed through descriptive-analytical techniques. The findings indicate that administrative sanctions are more frequently applied yet lack deterrent effect, while criminal and civil sanctions are rarely used due to evidentiary and procedural constraints. Weak institutional coordination, legal ambiguity, and limited public participation are identified as the main obstacles to effective enforcement. The study recommends reinforcing the principle of strict liability, harmonizing national and regional regulations, enhancing institutional capacity, and integrating legal enforcement with ecosystem-based management. Effective legal enforcement must be responsive to pollution complexity, ecologically just, and socially participatory.